Migration and its Effects on the Swedish Labour Market - Khattibová, Sára (2025)
The aim of this bachelor’s thesis is to assess the impact of migration on the Swedish labour market, focusing on employment, unemployment, wage levels, and occupational outcomes among foreign-born individuals and native-born Swedes. The topic is especially relevant in light of the increased migration after 2015 and the ongoing discussion about the role of migration in economic development. The thesis examines different types of migration, such as labour, family, humanitarian, and educational, and their influence on migrants’ integration into the labour market, with attention to region of origin and gender. The thesis is divided into three chapters. The first chapter presents the theoretical framework, defining key concepts related to migration, integration, and the labour market. The second chapter focuses on the development of migration in Sweden, describing major migration waves and shifts in migration policy. The third chapter is practical and analyses the position of migrants in the labour market in terms of employment and unemployment rates, income levels, sectoral representation, and types of jobs held by migrants. It also considers gender differences and compares migrants’ labour market outcomes with those of native-born Swedes. The methodology used is a combination of quantitative and qualitative secondary data from national and international sources to analyze how migration affects the Swedish labor market, using descriptive and comparative methods supported by graphs, charts, and academic literature.